Profitabilitas, Valuasi, dan Suku Bunga Pengaruhnya Terhadap Harga Saham Dengan Inflasi Sebagai Variabel Moderasi - Iren Meita; Dinda Ayu Annisa (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Stock prices are affected by various elements such as profitability, indicated by Return on Assets (ROA), valuation, shown by Price to Book Value (PBV), and interest rates. Beyond these factors, inflation acts as a moderating element to investigate its impact on both independent and dependent variables. This research focuses on companies within the banking sector that are listed on the Indonesia Stock Exchange. A quantitative methodology is implemented, utilizing secondary data sourced from the financial reports of banking institutions from 2021 to 2025. The purposive sampling method is employed, and the analysis is conducted using Eviews14 along with the Moderated Regression Analysis (MRA) technique, wherein inflation serves as the moderating element. The findings reveal that both profitability and valuation, as represented by ROA and PBV, influence stock prices; however, interest rates do not have an impact. Additionally, the MRA test indicates that inflation does not serve as a moderator for the relationship between ROA, PBV, and interest rates concerning stock prices.